Perovskite materials with improved stability and environmental friendliness for photovoltaics - Kumar, Sujit; Sharma, Sasanka Sekhor; Giri, Jayant; Makki, Emad; Sathish, T.; Panchal, Hitesh (Frontiers in Mechanical Engineering, 2024)
Finding innovative, stable, and environmentally acceptable perovskite (PVK) sunlit absorber constituents has developed a major area of study in photovoltaics (PVs). As an alternative to lead-based organic-inorganic halide PVKs, these PVKs are being researched for use in cuttingedge PVK solar cells. While there has been progress in this field as of late, there are still several scientific and technical questions that have yet to be answered. Here, we offer insights into the big picture of PVK toxicity/instability research, and then we discuss methods for creating stable, nontoxic PVKs from scratch. It is also believed that the processing of the proposed PVKs, which occurs between materials design and actual devices, poses novel challenges. PVK PVs that are both stable and ecologically benign can be created if these topics receive more attention. It's interesting to note that although perovskite solar cells (PSCs) have impressive power conversion efficiency, their commercial adoption is hindered by lead toxicity. Lead is a hazardous material that can cause harm to humans and the environment. As a result, researchers worldwide are exploring non-toxic lead-free photovoltaics (PSCs) for a sustainable and safe environment. To achieve this goal, lead in PSCs is replaced by non-toxic or less harmful metals such as tin, germanium, titanium, silver, bismuth, and copper. A study has been conducted that provides information on the characteristics, sustainability, and obstacles of replacing lead with these metals in PSCs. The paper also explores solutions for stability and efficiency issues in lead-free, nontoxic PSC commercialization, including altering manufacturing techniques and adding additives.Lastly, it covers the latest developments/future perspectives in lead-free perovskite solar cells that can be implemented in lead-free PSCs.